Market clustering and performance of U.S. OD markets - Cosmas, Alex (J Air Transp Manag, 2013)
We segment the U.S. OD markets into peer groups, using a statistical cluster analysis on OD city-pair data on the basis of market concentration, passenger volume and yield. The results show: 1) that high yield markets have, on average, consistently underperformed the industry in both passenger and revenue growth, whereas low yield markets have led the industry in both areas; and 2) mid-sized ODs have experienced higher average growth and lower volatility than the largest U.S. domestic ODs, which have accounted for the least revenue per passenger as compared to all other market types. Financial portfolio analysis indicates the prospect of long-term decision making based on OD market risk and return rather than the aggregated market share analysis used by airlines today.